PENGENALAN PROFESI APOTEKER DAN PENYULUHAN PEMANFAATAN TANAMAN OBAT DAUN SALAM UNTUK PENCEGAHAN DAN PENANGGULANGAN PENYAKIT ASAM URAT PADA MASYARAKAT DI PANCUR BATU KABUPATEN DELI SERDANG - Syafitri, Anggun; Rahmi, Sofia; Harahap, Nurul Dahlia; Amar, Ageng AZ; Hayati, Silmi (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Gout is a disease that affects the joints caused by the accumulation of uric acid crystals. High uric acid levels in the body can be caused by high protein levels. The increasing number of elderly people in Indonesia has prompted the government to formulate health policies aimed at improving their quality of life. Uric acid disease, especially gouty arthritis, is one of the common health conditions faced by the elderly, with a high preval_ence in various regions. The accumulation of uric acid crystals, caused by excessive purine consumption and lack of public awareness, is the main trigger for this condition. Frequently used pharmacological therapies have the risk of side effects, so safer alternatives are needed. One of them is the use of salam leaves (Syzygium polyanthum Wight) which contains flavonoids, functions as an antioxidant and inhibitor of the enzyme xanthine oxidase, which is proven to be able to reduce uric acid levels. Through community service activities in Salam Tani Village, Pancur Batu, education about gout and the utilization of salam leaves was carried out. The results showed an increase in community knowledge regarding the benefits of salam leaves in reducing uric acid levels and the role of pharmacists in health services. This education is expected to affect to reducing the preval_ence of gouty arthritis in the elderly.